Explanation of the Structural-functional Challenges of Comprehensive Health Centers in Babol City, Iran, Based on the Guidelines of the World Health Organization's Elderly-friendly Centers - Fatemeh Soleimani Kebria; Shima Sum; Aram Tirgar; Samaneh Pourhadi; Ahmad Delbari; Mohsen Shati; Elaheh Sadeghi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Primary care is the first main interface of health services for the elderly to maintain and improve their health. Therefore, it is essential to evaluate the appropriateness of the way to provide services for this population group, which is one of the most vulnerable classes of society. This study was conducted to explain the structural and functional challenges of comprehensive health centers in Babol City, based on the guidelines of the World Health Organization's elderly-friendly centers to plan aging-friendly. Methods & Materials The current research was a descriptive qualitative study using the content analysis method with a conventional approach. This research was conducted on elderly people who were referred to comprehensive health centers and their families as well as service providers in the form of in-depth semi-structured interviews until reaching the level of data saturation. Each interview was implemented immediately after implementation, and the content analysis of the interviews was conducted by determining conceptual units, accurate coding, and continuous comparison method until the formation of subgroups and main classes. Results In this study, 23 elderly people with an average age of 71.47±7.88, 5 family members, and 14 service providers participated. A total of 72 codes were extracted from all the interviews, which were divided into five main categories of structural factors, behavioral issues, educational characteristics, social support, and functional challenges during the analysis process. A total of twelve subgroups emerged for the five main classes. Conclusion Several underlying factors exist in the path of making comprehensive health centers elderly-friendly, and which will be impossible to achieve this issue without providing the conditions and eliminating the existing challenges. Therefore, the obtained components may help in identifying, and prioritizing needs, and choosing the type of interventions to adapt comprehensive health centers to the needs of the elderly.